2023
DOI: 10.1073/pnas.2219585120
|View full text |Cite
|
Sign up to set email alerts
|

GINS4 suppresses ferroptosis by antagonizing p53 acetylation with Snail

Abstract: Ferroptosis is an iron-dependent oxidative, nonapoptotic form of regulated cell death caused by the destruction of redox homeostasis. Recent studies have uncovered complex cellular networks that regulate ferroptosis. GINS4 is a promoter of eukaryotic G 1 /S - cell cycle as a regulator of initiation and elongation of DNA replication, but little is known about its impact on ferroptosis. Here, we found that GINS4 was involved in the regulation of ferroptosis in lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 61 publications
1
10
0
Order By: Relevance
“…S 15a , Supporting Information). DNA synthesis and replication was also enriched in the pathway and GO analysis, which was consistent with previous studies of erastin induced ferroptosis 63 , 64 (Fig. S 15a, b , Supporting Information).…”
Section: Resultssupporting
confidence: 91%
“…S 15a , Supporting Information). DNA synthesis and replication was also enriched in the pathway and GO analysis, which was consistent with previous studies of erastin induced ferroptosis 63 , 64 (Fig. S 15a, b , Supporting Information).…”
Section: Resultssupporting
confidence: 91%
“…In STRING based protein–protein interaction, the MCM6 protein significantly interacted with 10 different proteins 8 , 11 , 14 , 69 – 72 , 80 , 83 , 85 , 86 having the confidence score of ≥ 0.9 87 (Fig. 7 and Supplementary Table S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated that erastin remarkably reduced the proliferative activity of PCa cells. In addition, Fe 2+ is one of the essential factors of DNA replication, which is vital for cell survivability [38][39][40]. Consequently, we believed that erastin primarily transforms PCa cell proliferation by altering DNA replication.…”
Section: Discussionmentioning
confidence: 99%